Latitude, longitude and time zones - Phoenix Learning Group (Firm). ([Place of publication not identified] Phoenix Learning Group, 2015)
Gain an understanding of latitude and longitude. See how any place on Earth can be located by using meridians of longitude and parallels of latitude. Examine how time zones are determined by longitude and political boundaries.
Distributed by International Book Center.
Original copy in videocassette format.
Keywords: Earth sciences; Latitude; Longitude; Time -- Systems and standards